Democracy's reconstruction thinking politically with W.E.B. Du Bois - Balfour, Katharine Lawrence, 1964- (New York ; Oxford : Oxford University Press, 2011)
U.S. political theory rarely engages with black political thinkers, despite the fact that the problem of racial inequality is central to the entire enterprise of American political theory. To address this lacuna, Balfour focuses on the political thought of W.E.B. Du Bois.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Du Bois, W. E. B. -- 1868-1963 -- Political and social views; Du Bois, W. E. B. -- 1868-1963 -- Criticism and interpretation; Slavery -- United States; African Americans -- Politics and government; African Americans -- Social conditions; African Americans -- Civil rights; Critical theory -- United States; United States -- Politics and government